World Oil Prices and Indonesia Macroeconomic - W., M. Ichsandimas; Cahyadin, Malik (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2014)
The goal of this study is to look at the relation and contribution value, while the impact of world oil price on the macroeconomic Indonesian form 1980 to 2010. This Study used Vector Auto Regression (VAR) method and tool of VAR used are Impulse Response Function (IRF) and Variance Decomposition. The results of study finds a positive relation and statistically significant impact of world oil price on inflation and real GDP Indonesian, but not significant and negative relation on real exchange rates. World oil price has contribution value on the inflation, real exchange rates, Indonesia real GDP after first period.